Heidegger and Lacan - Dario Alparone; Valentina Lucia La Rosa (Language and Psychoanalysis, 2020)
Lacanian psychoanalysis cannot disregard its debts to philosophy, especially continental philosophy. Lacan’s conception of language is derived from multiple philosophical sources (i.e., Plato, Aristotle, Kant, Hegel, Kierkegaard) including Heidegger’s philosophy of language and pride of place. Heidegger’s view of language prepares the ground for reversing the relationship between language and human beings, overcoming common sense about language and the communicative model of language. Language is much more than a set of labels; it shapes the human world and structures social relations themselves. In addition, language acts as a social link. The function of language as a social link allows us to think of it in relation to the Law and the very function of this human subjectivity. In reference to the Other of the Law and language, the subject finds her recognition, and this implies that the language is not reducible to communication. The process of technical-scientific domination of Western institutions leads to a reduction of their functions to the formal aspects, which may lead to a reification of the human as well as a state of alienation.